An annotated checklist of European basidiomycetes related to white rot of grapevine (Vitis vinifera) - FISCHER, Michael; GONZÁLEZ GARCÍA, Vicente (Phytopathologia Mediterranea, 2015)
A considerable number of basidiomycetes are reported to live on Vitis vinifera. Detailed information about this relation dates back to the 19th and early 20th century. More recently, several basidiomycetes have been discussed as being associated with Grapevine Trunk Diseases, especially esca. On a European scale, we list 24 basidiomycetous taxa. Ten species are treated with respect to “life strategy and symptoms”, “host plants”, “geographic distribution”, “transmission and vectors”, “fruitbody characters” and “diagnosis”. Fourteen additional species are listed with their main features only. References are given both to data provided in the literature and from our observations. Fomitiporia mediterranea, and, to a lesser degree, Inonotus hispidus are discussed as primary pathogens. The remaining taxa, including Stereum hirsutum, Trametes hirsuta, and Schizophyllum commune, are considered as subordinate only, mainly causing white rot on already dead parts of grapevine trunks. With the data at hand, the ecological significance of Auricularia auricula-judae remains uncertain.